Analisis Hukum Terhadap Keabsahan Sertifikat Tanah Bengkok Dalam Kasus Penyerobotan Tanah di Desa Setupatok Kabupaten Cirebon - Nahdliya Farhani; Asmarani Ramli (CV Rewang Rencang, 2025)
An important case in Indonesian agrarian law, Supreme Court Decision No. 24 PK/TUN/2024, concerns a crooked land dispute in a customary village. The main focus of the case is the alleged land grabbing that occurs when individual title certificates are issued on land that is allegedly a collective asset of the village. The Supreme Court upheld the jurisdiction of the district court, not the government, to determine land ownership, and rejected the review filed by the Setupatok Village Government. This decision strengthens the validity of the legality of the certificate that has been issued until the district court decides otherwise. This makes it very difficult for indigenous villages to defend their crooked lands, thus requiring more thorough legal support for historical claims.